New Exact Solutions for the Wick-Type Stochastic Kudryashov–Sinelshchikov Equation - Ray, S. Saha; Singh, S. (Communications in theoretical physics, 2017)
In this article, exact solutions of Wick-type stochastic Kudryashov–Sinelshchikov equation have been obtained by using improved Sub-equation method. We have used Hermite transform for transforming the Wick-type stochastic Kudryashov–Sinelshchikov equation to deterministic partial differential equation. Also we have applied inverse Hermite transform for obtaining a set of stochastic solutions in the white noise space.